2001
DOI: 10.1046/j.1365-2249.2001.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin provides signal 3 to unprimed CD4+ T cells but failed to stimulate LPS primed B cells

Abstract: SUMMARYGrowing evidence has supported the conclusion that melatonin, a pineal hormone, modulates the immune function. In our previous study, we evaluated in vivo the potential role of melatonin in the regulation of the antigen specific T and B cells. In the present study, we observe that melatonin downregulated the expression of the co-stimulatory molecule B7-1 but not B7-2 on macrophages. Further, melatonin encouraged the proliferation of anti-CD3 antibody activated CD4 1 T cells only in the presence of antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 33 publications
2
42
1
2
Order By: Relevance
“…Melatonin has been demonstrated to be an effective anti-oxidant and free radical scavenger [17][18][19]. In addition, it has also been shown to have an anti-inflammatory effect and suppresses pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), and IL-6 [20][21][22][23][24][25]. Melatonin administration ameliorates the proinflammatory state and oxidative stress in diabetic fatty rats [26].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has been demonstrated to be an effective anti-oxidant and free radical scavenger [17][18][19]. In addition, it has also been shown to have an anti-inflammatory effect and suppresses pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), and IL-6 [20][21][22][23][24][25]. Melatonin administration ameliorates the proinflammatory state and oxidative stress in diabetic fatty rats [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently shown that the CD80 and CD86 expressed on B-cell lymphoma may promote or retard the growth by expressing anti-apoptotic and pro-apoptic molecules [26]. Further, melatonin, a pineal gland hormone can regulate the growth of T-cell lymphoma and normal T cell differentially [27].…”
Section: Resultsmentioning
confidence: 99%
“…Besides the release of proinflammatory Th-1 cytokines, such as IFN-Á and IL-2, administration of melatonin to antigen-primed mice increased the production of IL-10, indicating that melatonin also activates antiinflammatory Th-2-like immune responses [124,125]. It is not yet clear whether melatonin acts only on Th-1 cells or also on Th-2 cells.…”
Section: Melatonin Is a Circadian Immunoregulatory Signalmentioning
confidence: 99%